Mesenchymal Stem Cell Homing Into Intervertebral Discs Enhances the Tie2-positive Progenitor Cell Population, Prevents Cell Death, and Induces a Proliferative Response. Issue 23 (1st December 2019) - Wangler, Sebastian; Peroglio, Marianna; Menzel, Ursula; Benneker, Lorin M.; Haglund, Lisbet; Sakai, Daisuke; Alini, Mauro; Grad, Sibylle
Abstract : Study Design: Experimental study with human mesenchymal stem cells (MSCs) and intervertebral disc (IVD) tissue samples. Objective: This study aimed to characterize the effect of MSC homing on the Tie2-positive IVD progenitor cell population, IVD cell survival, and proliferation. Summary of Background Data: Homing of human MSCs has been described as potential alternative to MSC injection, aiming to enhance the regenerative capacity of the IVD. IVD cells expressing Tie2 (also known as CD202b or Angiopoietin-1 receptor TEK tyrosine kinase) represent a progenitor cell population with discogenic differentiation potential. However, the fraction of Tie2-positive progenitor cells decreases with aging and degree of IVD degeneration, resulting in a potential loss of the IVD's regenerative capacity. Methods: Human MSCs, isolated from vertebral bone marrow aspirates, were labeled and seeded onto the endplate of bovine IVDs and human IVD tissue. Following MSC migration for 5 days, IVD cells were isolated by tissue digestion. The fractions of Tie2-positive, dead, apoptotic, and proliferative IVD cells were evaluated by flow cytometry and compared to untreated IVDs. For human IVDs, 3 groups were investigated: nondegenerated (organ donors), IVDs of patients suffering from spinal trauma, and degenerative IVD tissue samples. Results: MSC homing enhanced the fraction of Tie2-positive IVD cells in bovine and human IVD samples. Furthermore, a proliferative response and lower fraction of dead cells were observed after MSC homing in both bovine and human IVD tissues. Conclusion: Our findings indicate that MSC homing enhances the survival and regenerative capability of IVD cells, which may be mediated by intercellular communication. MSC homing could represent a potential treatment strategy to prevent the onset of the degenerative cascade in IVDs at risk such as IVDs adjacent to a fused segment or IVDs after herniation. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the textHoming of mesenchymal stem cells (MSCs) from the endplate into the intervertebral disc (IVD) has been described as alternative intradiscal application route. Our findings indicate that the homed MSCs enhance the Tie2-positive disc progenitor cell population, prevent disc cell death, and induce a proliferative response in the IVD cells.